Development of a bone targeted thermosensitive liposomal doxorubicin formulation based on a bisphosphonate modified non-ionic surfactant. (17th August 2016) - Song, Heliang; Zhang, Jiabing; Liu, Xinrong; Deng, Tongming; Yao, Peng; Zhou, Shaobing; Yan, Weili
Abstract: Bone is among the most common sites of metastasis in cancer patients, so it is an urgent need to develop drug delivery systems targeting tumor bone metastasis with the feature of controlled release. This study aimed to delivery of thermosensitive liposomal doxorubicin to bone for tumor metastasis treatment. First, Brij78 (polyoxyethylene stearyl ether) was conjugated with Pamidronate (Pa). By incorporating Pa-Brij78 to DPPC/Chol liposomes, we developed Pa surface functionalized liposomes. The Pa-Brij78/DPPC/Chol liposomes (PB-liposomes) exhibited a stronger binding affinity to hydroxyapatite (HA), a major component of bone, than Brij78/DPPC/Chol liposomes (B-liposomes). Doxorubicin (Dox) was then encapsulated in PB-liposomes and the results demonstrated complete release of Dox from PB-liposomes or the complex of HA/PB-liposomes within 10 min at 42 °C. Next, human lung cancer A549 cells were treated with the thermosensitive complex of HA/PB-liposomes/Dox to mimic tumor bone metastasis treatment through bone targeted delivery of therapeutic agents. Pre-incubation of HA/PB-liposomes/Dox with mild heat at 42 °C induced subsequent higher cytotoxicity to A549 cells than incubation of the same complex at 37 °C, suggesting more active drug release triggered by heat. In conclusion, we synthesized a novel surfactant Pa-Brij78 and it has the potential to be used for development of a bone targeted thermosensitive liposome formulation for treatment of tumor bone metastasis.